2021
DOI: 10.1590/1678-4162-12482
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and morphometric study of goat middle ear ossicles (Capra aegagrus hircus)

Abstract: The social and economic roles of goat farming in Northeastern Brazil, allied to the fact that the use of goat middle ear ossicles for research and human ear surgery training has not yet been proposed, justify the study of their applicability as an experimental model. The middle ears of 19 goats (Capra aegagrus hircus) from the bone collection of the Laboratory and Didactic Anatomy Museum of Domestic and Wild Animals of the Federal University of Vale do São Francisco (UNIVASF) were dissected. The malleus, incus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Santos et al. (2021) detected a significant correlation between the length of the malleus with the height of the malleus and width of the stapes, between the length of the incus with height of the incus, length and height of the stapes, between length of the stapes with height of the stapes in goats. In our study, a strong correlation was found between the length of the malleus and the length of the manubrium mallei, between the length of the incus with the lengths of the long crus and corpus incudis, between the length of the stapes with the lengths of the rostral crus, caudal crus, caput stapedis, length and width of the intercrural foramen.…”
Section: Discussionmentioning
confidence: 98%
“…Santos et al. (2021) detected a significant correlation between the length of the malleus with the height of the malleus and width of the stapes, between the length of the incus with height of the incus, length and height of the stapes, between length of the stapes with height of the stapes in goats. In our study, a strong correlation was found between the length of the malleus and the length of the manubrium mallei, between the length of the incus with the lengths of the long crus and corpus incudis, between the length of the stapes with the lengths of the rostral crus, caudal crus, caput stapedis, length and width of the intercrural foramen.…”
Section: Discussionmentioning
confidence: 98%